Monitoring of general anesthesia by qCON and qNOX indices versus conventional clinical parameters in urological surgery: A randomized controlled clinical trial - Himalaya Dutta,; Suchismita Mallick,; Baisakhi Laha,; Sarbari Swaika,; Uday Sankar Mandal,; Sarmila Ghosh, (Asian Journal of Medical Sciences, 2024)
Background: Awareness during anesthesia is a major anesthetic concern. Depth of anesthesia is commonly assessed in clinical practice by the patient’s clinical signs and symptoms such as blood pressure, heart rate variability, and body movement. At present, many studies have focused on qCON monitoring for sedative depth, but only a few studies have focused on qNOX monitoring for analgesic depth. Aims and Objectives: The aim of the present study was to evaluate the relative efficacy of qCON and qNOX versus commonly used vital signs such as blood pressure and heart rate in monitoring the anesthetic depth and analgesia. Materials and Methods: A total of 100 patients of either sex and of ASA Physical status I & II, scheduled for urogenital surgeries, were selected and randomly placed into two groups. Group A was monitored by conventional clinical technique and Group B was monitored by qCON and qNOX indices. The primary outcome was the total dose of propofol and fentanyl required to maintain the depth of anesthesia and analgesia. The secondary outcomes were propofol and fentanyl adjustment frequency, infusion duration, and quality of recovery from anesthesia. Results: Results showed statistically significant differences between the two groups in mean dose of both propofol (P=0.000) and fentanyl (P=0.006), adjustment frequency of both propofol (P=0.000) and fentanyl (P=0.010), time required to voluntary eye-opening (P=0.000) and extubation time (P=0.000) and visual analog scale score (P=0.000). There was no statistically significant difference found in infusion duration (P=0.317) and Ramsay Sedation Score (P=0.709) between the groups. Conclusion: Using the qCON and qNOX indices, an anesthesiologist can monitor the depth of anesthesia and analgesia more effectively and can adjust the anesthetic or analgesic drug dosing in a better possible way with lesser requirement of drugs than with conventional clinical monitoring.